(untitled) (Update Dental College Journal, 2015)
The aim of this study is to compare the tissue response between the ridgelap pontic and modified ridgelap pontic. Total patients were 40. The fixed prosthesis were cemented by temporary cementing material. After providing the treatment, instruction on maintenance of prosthesis. Patients were visited and studied after 6 weeks, 12 weeks and 6 months to observe the condition of tissue response beneath pontic. The following necessary data were collected in respect of the condition of tissue beneath the pontic, color of gingiva. The modified ridgelap pontic is better than ridgelap pontic regarding tissue response. The tissue response with the ridgelap surface of the pontic of fixed partial denture in 1st molar missing tooth enhanced the condition of the mucous membrane beneath the tissue surface of the pontic, condition of the abutment tooth, between ridge surface of the pontic and mucosa overlying the edentulous ridge achieved better success regarding fixed partial denture. Update Dent. Coll. j: 2015; 5 (1): 15-20